Rekonstruksi Kurikulum dalam Pendidikan Alternatif : Analisis Praktik Pembelajaran di Sanggar Anak Alam (SALAM) Yogyakarta - Salsabilla Firdaus; Pascalia Putria Hanindya; Erfina Okta Auliasari; Maylani Eka Putri; Moh Krisna Setiawan Nugraha; Muhammad Adam Al Faruh; Okta Hadi Nurcahyono (Journal of Education Research, 2026)
Standardized formal education systems frequently fail to accommodate diverse learning interests and needs, necessitating more flexible, child-centered learning models. This study aims to describe the implementation of research-based learning in fostering self-directed learning among students at Sanggar Anak Alam (SALAM) Yogyakarta. A qualitative approach with a case study method was employed; data were collected through observations, in-depth interviews, and documentation involving the founder, principal, facilitators, parents, and students, then analyzed through data reduction, display, and conclusion drawing. Findings reveal that research-based learning is implemented by allowing students to select research topics according to their interests, following a learning cycle of experiencing, doing, expressing, analyzing, concluding, and applying. This approach fosters self-directed learning by developing students' abilities to set learning goals, manage learning activities, seek resources independently, reflect on learning, and take responsibility for both the process and outcomes.